2012
DOI: 10.1063/1.4770357
|View full text |Cite
|
Sign up to set email alerts
|

The role of confinement on stress-driven grain boundary motion in nanocrystalline aluminum thin films

Abstract: The role of confinement on stress-driven grain boundary motion in nanocrystalline aluminum thin films 3D molecular dynamics simulations are performed to investigate the role of microstructural confinement on room temperature stress-driven grain boundary (GB) motion for a general population of GBs in nanocrystalline Al thin films. Detailed analysis and comparison with experimental results reveal how coupled GB migration and GB sliding are manifested in realistic nanoscale networks of GBs. The proximity of free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 85 publications
(110 reference statements)
1
14
0
Order By: Relevance
“…In small-grained metals, numerous experimental studies have provided convincing evidence that stress-assisted GB migration induces grain growth even at low temperature [1][2][3][4][5][6][7][8][9]. Contrary to lattice dislocation mechanisms, which have been well documented, GB migration under stress operates by different "coupling modes" [10][11][12][13] that may depend on the GB structure.…”
Section: Introductionmentioning
confidence: 96%
“…In small-grained metals, numerous experimental studies have provided convincing evidence that stress-assisted GB migration induces grain growth even at low temperature [1][2][3][4][5][6][7][8][9]. Contrary to lattice dislocation mechanisms, which have been well documented, GB migration under stress operates by different "coupling modes" [10][11][12][13] that may depend on the GB structure.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, we always observe mechanically-induced grain growth with our strain localization here, but such behavior could also be influence by sample size. Using MD simulations of thin film geometries, Gianola et al 55 found that mechanically-induced grain coarsening is substantially enhanced near free surfaces and multiple authors showed that this surface effect occurs over a length that is roughly the order of the grain size. 55,65 Our goal here is to check that our observations are not an artifact of our relatively limited sample size.…”
Section: B Effect Of Testing Conditions On Strain Localizationmentioning
confidence: 99%
“…As such, a 23 nm mean grain size provided a good compromise between small grain size and a distance of about one grain diameter from the surface [256]. In our samples, the presence of many grains through the film thickness limits the importance of any free surface effects.…”
Section: Resultsmentioning
confidence: 95%